(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This paper describes the development of a low-cost, single-lead electrocardiograph (ECG) device based on the Arduino microcontroller platform and the AD8232 analog front-end integrated circuit. The device makes it possible to record the electrical activity of the heart in real time, distinguish the P, QRS and T waves, and calculate the heart rate (HR). The acquired signal is cleaned using digital filtering — a 50 Hz notch filter that suppresses mains interference and a 0.5–40 Hz band-pass filter — and is visualized on a personal computer. The experimental results showed that the developed device provides an ECG signal of sufficient quality for educational and preliminary screening purposes. The cost of the device is significantly lower than that of industrial counterparts, which opens up prospects for its use in the educational process and in regions with limited resources.